A Critical History of Poverty Finance: Colonial Roots and Neoliberal Failures - Nick Bernards (Pluto Press, 2022)
The definitive account of the history of poverty finance' - Susanne Soederberg Finance, mobile and digital technologies - or 'fintech' - are being heralded in the world of development by the likes of the IMF and World Bank as a silver bullet in the fight against poverty. But should we believe the hype? A Critical History of Poverty Finance demonstrates how newfangled 'digital financial inclusion' efforts suffer from the same essential flaws as earlier iterations of neoliberal 'financial inclusion'. Relying on artificially created markets that simply aren't there among the world's most disadvantaged economic actors, they also reinforce existing patterns of inequality and uneven development, many of which date back to the colonial era. Bernards offers an astute analysis of the current fintech fad, contextualised through a detailed colonial history of development finance, that ultimately reveals the neoliberal vision of poverty alleviation for the pipe dream it is.
Keywords: 330; Microfinance; Critical Development Studies; Development Studies; G20; IMF; World Bank; Poverty Alleviation; Africa; Fintech; Digital Technologies; Financial Technologies; Microinsurance; Fight against poverty